2021
DOI: 10.2991/assehr.k.210909.100
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition Against Angiotensin Converting Enzyme by Sonchus arvensis Water Extract and Fractions as Antihypertension

Abstract: Hypertension is a condition in which a person has an elevating in blood pressure above normal, resulting in an increasing in morbidity and mortality. One mechanism of treating hypertension is by inhibiting the formation of angiotensin converting enzyme (ACE). Sonchus arvensis, known as tempuyung, widely used in treating various diseases, such as diuretic, anti-inflammatory, and antihypertensive The purpose of this study was to test the in vitro inhibition of single extracts, namely polar layer BuOH, semipolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Afrianti et al [4] demonstrated that the ethanol extract of sembung leaves could effectively reduce blood pressure in white male rats, with the most significant effect observed at a dose of 500 mg/kg BW. Trivadila et al [5] discovered that the polar layer of tempuyung leaf extract exhibited antihypertensive properties comparable to the synthetic drug captopril when tested using the in vitro method.…”
Section: Introductionmentioning
confidence: 99%
“…Afrianti et al [4] demonstrated that the ethanol extract of sembung leaves could effectively reduce blood pressure in white male rats, with the most significant effect observed at a dose of 500 mg/kg BW. Trivadila et al [5] discovered that the polar layer of tempuyung leaf extract exhibited antihypertensive properties comparable to the synthetic drug captopril when tested using the in vitro method.…”
Section: Introductionmentioning
confidence: 99%